Comparison of physicochemical, mechanical and antioxidant properties of polyvinyl alcohol films containing green tealeaves waste extracts and discarded balsamic vinegar. (March 2020) - Quilez-Molina, Ana Isabel; Heredia-Guerrero, José Alejandro; Armirotti, Andrea; Paul, Uttam C.; Athanassiou, Athanassia; Bayer, Ilker S.
Graphical abstract: Highlights: Formic acid extracts high levels of catechins from used green tea. Packaging films were developed using tea and vinegar waste in polyvinyl alcohol. The films displayed strong and effective antioxidant properties. Discarded balsamic vinegar is a good plasticizer for polyvinyl alcohol. Abstract: Plant origin processed food wastes like tealeaves, coffee, fruit or wine pomace can be very rich in antioxidants and antiseptics. The goal of this work is to develop antioxidant polyvinyl alcohol (PVA) packaging films using wastes generated from used green tealeaves and discarded (quality control failed) balsamic vinegar and compare their properties. Both components were separately incorporated into PVA via simple one-pot fabrication approach. Formic acid was used to extract potential antioxidants from dried waste tealeaves, simultaneously dissolving PVA. Discarded vinegar was simply added to a water solution of PVA and in both cases antioxidant films were produced by solution casting and drying. PVA films were loaded up to 50 wt.% by both waste components allowing maximum utilization of useful organics from both discarded foodstuffs. Formic acid extracted gallated catechins with very high yields (>95 %) from tealeaves waste with excess amounts of epigallocatechin gallate (EGCG). Moreover, discarded balsamic vinegar was found to be an effective plasticizer for PVA with 150 % elongation levels. Tealeaves waste exhibited better inhibitory concentration levels (IC50; 73.1 μg/ml) than discarded balsamic vinegar (1846.7 μg/mL), comparable to synthetic commercial antioxidants. They also improved oxygen barrier properties of PVA, regardless of the solvent used. These films could be potentially suitable for antioxidant food packaging applications.